Rancang Bangun Sistem Manajemen Transaksi Bengkel (Studi Kasus: UKM HMS Motor) - Fachruddin . (LPPM STIKOM Dinamika Bangsa, 2017)
Bengkel HMS motor is a bussiness that sells spare parts, oil and serve the service of motor service. In stock replenishment parts repair shop is buying spare parts, oil from supplier.Namun, in the activity of all transactions are still recorded manually. In the transaction service or customer acceptance only rely on paper transaction proof, so that on service service process still often happened error of transaction and stock data. Based on that, hence this research formulate problem to build an information system application which function as recording, monitoring, until processing data of HMS Motor Workshop. The first stage of literature study on information system, uml modeling, oop, code igniter and mysql. The next stage is the process of collecting data. This process is done by collecting workshop transaction data, transaction processing manually. As for system modeling method used using UML (Unified Modeling Language). After the design is completed next is the construction of an information system application that serves as the recording, monitoring, until data processing on repair services that exist in the Workshop HMS Motor.Proses include the design of user interface, coding and testing. To evaluate output results, the system will be tested using blackboxtesting testing. And the last is the stage of preparing reports after the research activities produce a system result, evaluation and analysis.